Worry as the new normal. Generation Z facing its future through the educational process - Sophie Agulhon; Gerardo Romo Morales (Senderos Pedagogicos)
This contribution examines the characteristics of Generation Z (Gen Z) and the emotional imagination of its members about their professional future. The aim of this paper is to provide elements for a better understanding of the role of education in shaping the future projections Gen Z members. To do this, we analyze aspects related to their emotions and sensitivity, placing special emphasis on a particular emotion: worry. And we do this after realizing that there is not much literature that analyzes the emotions involved in the visions of the future that awaits them. In methodological terms, we use an international research protocol (applied to young people from Mexico and France) that we developed to collect young people's opinions about themselves and their future, and finally, we present some of the most significant results that have to do with worry and resilience